DEVELOPMENT OF TECHNOPRENEURSHIP LEARNING TOOLS IN VOCATIONAL HIGH SCHOOLS: A SYSTEMATIC REVIEW OF MODELS, COMPONENTS, AND IMPLICATIONS: Pengembangan Perangkat Pembelajaran Technopreneurship di SMK: Tinjauan Sistematis terhadap Model, Komponen, dan Implikasi - Febri Handoyo; Isnandar Isnandar; Wahyu Sakti Gunawan Irianto; Widiyanti Widiyanti; Siti Salina Mustakim (SOSIOEDUKASI, 2026)
This study aims to map the trends in the development of technopreneurship learning tools in Vocational High Schools by analyzing the development models, core components, and pedagogical implications to identify research gaps. Using the Systematic Literature Review (SLR) method with the PRISMA approach and PICo framework, this study selected five relevant articles from Google Scholar, Semantic Scholar, and Dimensions databases for the period 2021-2025. The results of the data analysis show that the ADDIE and Borg & Gall development models are the most dominant because of their systematic structure in ensuring technical and pedagogical quality. The main components of the learning tool focus on three main aspects: digital technology integration, strengthening 21st-century skills (4Cs), and technical mastery of entrepreneurial management. Pedagogically, the implementation of these tools has been proven effective in improving student learning outcomes, motivation, and independence, as well as transforming the role of teachers into facilitators in the digital ecosystem. Despite the positive impact, a research gap was found in that current development is still limited to independent modules and has not touched on the formation of a comprehensive digital entrepreneurship ecosystem to overcome the low level of students' digital-preneurship skills in the field.